Analisis Refocusing dan Realokasi Anggaran Kegiatan di Masa Pandemi Covid-19 Pada Dinas Tanaman Pangan Hortikultura dan Peternakan Kabupaten Bengkalis - Asmaria Ulfa; Nur Anita (Universitas Teknokrat Indonesia, 2022)
AbstractThis study aims to find out 1) How is the process of refocusing and reallocating the budget at the Horticultural Food Crops and Livestock Service Office of Bengkalis Regency, 2) How is the impact of refocusing and budget reallocation on the Horticultural Food Crops and Animal Husbandry Department of Bengkalis Regency 3) To find out the strategies carried out by the Plantation Service. Horticultural Food and Livestock in Bengkalis Regency after refocusing and reallocating the budget for handling COVID-19. This research is a descriptive study using qualitative methods. The results showed that the refocusing and reallocation of activity budgets at the Bengkalis Regency Horticulture and Animal Feed Crops Service in handling COVID-19 was carried out by diverting the budget for mass gathering activities such as official travel, training and guidance into assistance activities to the community in the form of food crops, seeds and fertilizers and drugs in animal husbandry. Keywords: COVID-19 Pandemic, Refocusing, Budget Reallocation AbstrakPenelitian ini dilakukan bertujuan untuk mengetahui 1) Bagaimana proses refocusing dan realokasi anggaran pada dinas Tanaman Pangan Hortikultura dan Peternakan Kabupaten Bengkalis, 2) Bagaimana dampak refocusing dan realokasi anggaran Pada dinas Tanaman Pangan Hortikultura dan Peternakan Kabupaten Bengkalis 3) Untuk Mengetahui Strategi yang dilakukan Dinas Tanaman Pangan Hortikultura dan Peternakan Kabupaten Bengkalis setelah dilakukan refocusing dan realokasi anggaran untuk penanganan COVID-19. Penelitian ini merupakan penelitian deskriptif dengan menggunakan metode kualitatif. Hasil penelitian menunjukan refocusing dan realokasi anggaran kegiatan pada Dinas Tanaman Pangan Hortikultura dan Peternakan Kabupaten Bengkalis dalam penanganan COVID-19 dilakukan dengan cara mengalihkan anggaran kegiatan yang bersifat pengumpulan massa seperti perjalanan dinas, pelatihan dan bimbingan menjadi kegiatan bantuan kepada masyarakat berupa tanaman pangan, bibit serta pemupukan dan obat-obatan pada peternakan hewan Kata kunci : Pandemi COVID-19, Refocusing, Realokasi Anggaran.